2020
DOI: 10.1136/bcr-2020-236536
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome associated with COVID-19 infection: a case from the UK

Abstract: Originating from Wuhan, China, COVID-19 has rapidly spread worldwide. Neurological manifestations are more commonly associated with severe COVID-19 infection. Guillain-Barré syndrome (GBS) is a rare immune-mediated postinfectious neuropathy. It has been reported as a possible rare complication of COVID-19. We report a case of GBS associated with COVID-19 in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 12 publications
0
46
0
3
Order By: Relevance
“…Moreover, cytoalbuminologic dissociation of the CSF is a characteristic finding in GBS, pointing to nerve root involvement. Analysis of CSF usually reveals normal white cell count and increased protein concentrations [ 95 , 96 ]. Results of electrophysiological studies are frequently consistent with a demyelinating polyradiculoneuropathy and/or axonal damage.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, cytoalbuminologic dissociation of the CSF is a characteristic finding in GBS, pointing to nerve root involvement. Analysis of CSF usually reveals normal white cell count and increased protein concentrations [ 95 , 96 ]. Results of electrophysiological studies are frequently consistent with a demyelinating polyradiculoneuropathy and/or axonal damage.…”
Section: Resultsmentioning
confidence: 99%
“…After review of the 242 documents, we identified 430 patients with COVID-19 diagnosed based on PCR or serologic testing who had acute neurological symptoms prompting CSF testing [ [5] , [6] , [7] , [8] , [9] , [10] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , …”
Section: Resultsmentioning
confidence: 99%
“…Although the CSF RBC count was only reported for 61/430 (14%) patients [ 22 , 28 , 29 , 31 , 35 , 39 , 40 , 44 , 73 , 74 , 77 , 78 , 81 , 89 , 92 , 102 , 110 , 118 , [120] , [121] , [122] , [123] , 128 , 133 , 134 , [138] , [139] , [140] , 156 , 165 , 166 , [172] , [173] , [174] , [175] , [176] , 180 , 184 , 188 , 191 , 192 , 198 , 202 , 204 , 208 , 215 , 220 , 225 , 227 , 233 , 241 , 242 , 246 ], the CSF white blood cell (WBC) count was provided for 409/430 (95%) patients, 270 (66%) of whom had >0 cells/μL, >1 WBC:1,000 RBC or were noted to have “pleocytosis” ( Fig. 3 ) [ [5] , [6] , [7] , [8] , 10 , 13 , [15] , [16] , [17] , [18] ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neurological and psychiatric complications of COVID-19 are widely reported; these include encephalitis, cerebral infarction, delirium, depression, delirium, psychosis Guillain-Barré syndrome [16][17][18][19][20], Miller-Fisher syndrome, and etcetera [19,[21][22][23][24][25][26][27][28]. In at least three cases the COVID-19 brought with it symptoms of clinical Parkinsonism demonstrating therefore a potential direct link between the SARS-CoV-2 infection and neurodegeneration (see [29] for details).…”
mentioning
confidence: 99%